Chinese medicine PaBing-II protects human iPSC-derived dopaminergic neurons from oxidative stress - Wu, Shouhai; Rong, Cuiping; Lin, Ruishan; Ji, Kaiyuan; Lin, Tongxiang; Chen, Weimin; Mao, Wei; Xu, Yang (Frontiers in Immunology, 2024)
PaBing-II Formula (PB-II) is a traditional Chinese medicine for treating Parkinson's disease (PD). To investigate the mechanisms underlying the therapeutic benefits of PB-II in patients with PD, we developed human dopaminergic neurons (DAn) oxidative damage models by treating human induced pluripotent stem cells (hiPSCs) derived DAn with H2O2 as well as the 6-hydroxydopamine (6-OHDA)-induced PD rat model. Through in vitro and in vivo studies, we demonstrate that PB-II significantly protects DAn from oxidative stress and inflammation via Nrf2 pathway activation, and is manifested as a treatment for Parkinson's disease.